The Moral Boundary Drawing of Class: Social Inequality and Young Precarious Workers in Poland and Germany. (June 2021) - Trappmann, Vera; Seehaus, Alexandra; Mrozowicki, Adam; Krasowska, Agata
This article explores the relational and moral aspects of the perception of class structure and class identifications by young people in objectively vulnerable labour market conditions in Poland and Germany. Drawing on 123 biographical interviews with young people in both countries, it demonstrates that young precarious Poles and Germans tend to identify themselves against the 'middle class' – understood variously in the two countries – and attribute the sources of economic wealth and social status in their societies to individual merits and entrepreneurship. Positioning oneself in the broad middle and limited identification with the precariat is explained by the youth transition phase, country-specific devaluation of class discourses and the effects of individualisation.